Sosialisasi Pencegahan Stunting Melalui Upaya Pemantauan Tumbuh Kembang Balita di TK Aisyiyah Kabupaten Sidenreng Rappang - Nasrayanti Nurdin; Resky Devi Akib; Chandra Ariani Saputri; Ariyana Ariyana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Stunting is a serious public health problem around the world. One of the targets of the Sustainable Development Goals (SDGs) is to eliminate hunger and all forms of malnutrition by 2030. The target to be set by 2025 is to reduce the stunting rate by 40%. Stunting is a condition of length or lack of height when compared to age in children under five due to chronic malnutrition, especially in the first 1000 days of life (HPK). The toddler period is a golden age that is very important for the human life process because this toddler period has a great influence on the success of the child's next growth and development process. Parents and teachers are expected to monitor the growth and development of children. Some of the impacts of children's growth and development that are not suitable for their age include inhibiting brain development. Therefore, the purpose of this service is to conduct growth and development counseling for children under five. This activity was carried out in October 2022 at Aisyiyah Sidenreng Rappang Kindergarten with the target of mothers who have children aged 0-5 years. Mother's activities are in the form of how to check the development and growth of toddlers. The first stage is to show how to monitor the growth and development of toddlers and continued with the second stage of conducting growth checks and camping together between parents and teachers. The results of the examination carried out found that there were some parents who did not understand the growth and development disorders of children and there were toddlers whose nutritional status was lacking. Early detection of growth and development in toddlers is very important to do as early as possible.